In situ biofortification of folate in sorghum with Lactobacillus plantarum and its microbiome analysis using 16s rRNA gene sequencing - Buys, E.M. (Elna Maria) (University of Pretoria, 2020)
Dissertation (MSc (Food Science))--University of Pretoria, 2020.